COMPARATIVE ANALYSIS OF INDOFOOD CBP'S CASH FLOW BEFORE AND DURING COVID-19 - Semma Aprilyah; Mariam Makmur; Ari Ayu (Universitas Ichsan Sidenreng Rappang, 2025)
Covid-19 is a virus that has a high transmission rate. The emergence of Covid-19 in March 2020 caused its negative impact to be felt by many people in the world, including Indonesia. One of the impacts is the economy of PT. Indofood CBP Successfully Prosperous. This research aims to analyze the comparison of cash flows of PT. Indofood Before and During Covid-19. The research design used is comparative with quantitative secondary data. The data collection method is documentation. The documents used are official documents in the form of company financial reports. The ratio used to measure financial performance is the cash flow ratio. This research uses normality tests and hypothesis testing. If the distribution is normal then the Paired Sample T-Test is used and if the distribution is not normal then the Wilcoxon Signed Rank Test is used. The research results show that the cash flow ratio in the company PT. Indofood CBP Sukses Makmur in the period before and during Covid-19 did not experience significant changes or there were no differences before and during Covid-19, so the hypothesis is rejected.